Formulation and test of mosquito repellent lotion from the extract of kecombrang (Etlingera elatior (Jack)) and beluntas (Pluchea indica) leaves extract - Taurhesia, Shelly; Endah, Endah; Basuki, Witono; Djamil, Ratna (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Dengue fever is an infectious disease which is transmitted by Aedes aegypti mosquitoes and commonly occurs in Indonesia. The use of natural ingredients for mosquito repellent is becoming a trend. Kecombrang (Etlingera elatior (Jack)) is known as a medicinal plant which contains alkaloids, saponins, tannins, phenolics, flavonoids, triterpenoids, steroids, and glycosides. Beluntas (Pluchea indica) contains tannins, alkaloids, flavonoids, phenols, saponins and essential oils. This study aims to develop mosquito repellent lotion using combined leaf extracts of E. elatior and P. indica at different ratios (1:1; 1:2; 2:1). The materials used in this study were E. elatior and P. indica leaves, Aedes aegypti mosquitoes, 96% ethanol, stearic acid, triethanolamine, white oil, methyl paraben, cetyl alcohol, and distilled water. The repellent activity is tested using a standard method of WHO, comparing control group and treatment group, repeating for four times, then the protection level was calculated. The three formulas of lotion fulfilled both physical and chemical requirements and had a repellent activity of above 80%. The formulae of F3, a lotion containing both E. elatior and P. indica leaf extracts of 2:1, gave the highest protection of 88.1%.